Programmatic Lattice Generation for Additive Manufacture. (2015) - M Millan, Matthew; Jurg, Marten; Leary, Martin; Brandt, Milan
Abstract: Advances in additive manufacturing hardware have enabled the creation of lattice structures for engineering purposes; however the use of standard CAD software for the design of lattice structures is grossly inefficient, time consuming, and can lead to processing issues. To assist designer engineers that intend to implement large lattice structures a highly customisable free open source method of generating periodic lattice structures directly to the generic STL format has been developed. Programmatic method also offers a significant advantage to designers seeking to optimise or conduct finite element simulations on lattice structures allowing a batch export of both STL parts and a geometrically equivalent FE beam models.